Discourse and Subjectivation Theory Meet Group Discussions: Methodological Considerations for a New Connection - Geipel, Karen (Forum Qualitative Sozialforschung / Forum: Qualitative Social Research, 2019)
While there is a growing belief that the data used in pedagogical discourse and subjectivation research is made up of statements by speakers from interviews and ethnographic observations, group discussions, represent a type of material in this field that has seldom been taken into account to date. Rather, group discussions have so far been closely linked to the documentary method, which is based on assumptions of the praxeological sociology of knowledge. In contrast, a methodological justification of speaking in group discussions by discourse- and subjectivation-theoretical figures of thought in the German-speaking and international research landscape is still lacking. In this article, I combine a poststructuralist perspective with group discussions. I outline methodological assumptions, which have so far established the procedure on the basis of the documentary method, and also carry out central discourse and subjectivation-theoretical premises of a perspective oriented towards the work of Judith BUTLER. By subsequently juxtaposing these approaches , I show to what extent basic assumptions are modified in the course of a post-structuralizing perspective and clarify the potential for poststructuralist discourse and subjectivation analyses. I suggest understanding utterances in group discussions as executions of situated discursive practices and places of processes of subjectivation.